Design of novel hybrid 2D nanomaterials for optical, optoelectronic and micro-electro-mechanical systems applications - Elloh, V.W.; Gebreyesus, G.; Dodoo-Arhin, D.; et al. (Hybrid Advances, 2023)
Novel hybrid 2D class of ternary nano heterostructures have been designed by mixing aluminium nitride (AlN), and boron nitride (BN) with 2D graphene to design innovative 2D nano heterostructures for applications in electronics and other industries. The structural stability and electronic properties of these nano heterostructures have been analysed using “first-principles based calculations done in the framework of density functional theory. Different structural patterns have been analysed to identify the most stable nano heterostructures. It is more energetically favourable that the aluminium nitride and boron nitride atom chains occupy the positions of the carbon atoms in a clustered pattern in the nanoheterostructures. Carbon atom chains sandwiched between aluminium nitride and boron nitride chains of atoms are a preferred choice over isolated chains of BN, AlN and CC in the nanoheterostructures. The calculated band gaps of the novel nanoheterostructures are found to be 0.87, 0.43 and 0.65 eV respectively. These novel hybrid 2D nano-heterostructures are energetically favoured materials with both direct and indirect band gaps. They have potential applications in nanoscale semiconducting and optoelectronic devices, notably optical, optoelectronic and micro-electro-mechanical systems.
Research Article
Keywords: Hybrid; Microelectromechanical; Design; Novel hybrid 2D nanoheterostructures; Optoelectronics